Missionary education : historical approaches and global perspectives - Christiaens, Kim, 1985-; Goddeeris, Idesbald, 1972-; Verstraete, Pieter (Leuven studies in mission and modernity, 2021)
Missionaries have been subject to academic and societal debate. Some scholars highlight their contribution to the spread of modernity and development among local societies, whereas others question their motives and emphasise their inseparable connection with colonialism. In this volume, fifteen authors - from both Europe and the Global South - address these often polemical positions by focusing on education, one of the most prominent fields in which missionaries have been active. They elaborate on Protestantism as well as Catholicism, work with cases from the 18th to the 21st century, and cover different colonial empires in Asia and Africa. The volume introduces new angles, such as gender, the agency of the local population, and the perspective of the child.